2018
DOI: 10.17113/ftb.56.03.18.5540
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Antidiabetic Food Produced via Solid-State Fermentation of Tartary Buckwheat using L. plantarum TK9 and L. paracasei TK1501

Abstract: SummaryDiabetes is a chronic metabolic disease characterized by hyperglycaemia and a number of potential complications that significantly reduce the patient’s quality of life. In this study, we produced an antidiabetic functional food from Tartary buckwheat fermented by Lactobacillus plantarum TK9 and L. paracasei TK1501. The results of an orthogonal experimental design indicated that the three factors with the largest effects on the growth of L. plantarum TK9 and L. paracasei TK1501 in solid-state fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Previous studies on probiotics have demonstrated that some strains present an inhibitory effect on α-glucosidase activity [77,124], and the same was confirmed in EPS and cell-free supernatant. In the same line, supernatants from LABs also exhibited DPP-IV inhibitory activity, which was also described in fermented products [125]. At this point, scientists must consider postbiotics as a potential line of research for the development of natural AGI and DPP-IV inhibitors.…”
Section: Discussionmentioning
confidence: 76%
“…Previous studies on probiotics have demonstrated that some strains present an inhibitory effect on α-glucosidase activity [77,124], and the same was confirmed in EPS and cell-free supernatant. In the same line, supernatants from LABs also exhibited DPP-IV inhibitory activity, which was also described in fermented products [125]. At this point, scientists must consider postbiotics as a potential line of research for the development of natural AGI and DPP-IV inhibitors.…”
Section: Discussionmentioning
confidence: 76%
“…As far as we are concerned, there are no reports of an antagonistic effect between L. paracasei and the most common LAB in cassava. They have even been used together in other foodstuffs [21]. This suggests that pH differences can be attributed to L. paracasei inoculation used during this study.…”
Section: Dough Fermentationmentioning
confidence: 98%
“…Oligosaccharides (oligofructose and galacto-oligosaccharide) were reported to support the growth of Lactobacillus as prebiotics [123]. Green tea extract [124] and buckwheat-resistant starch [125] were reported to promote the growth of Lactobacillus in a fermentation assay. On the other hand, in an in vitro fermentation assay using gut microbiota, it was reported that fucosylated chondroitin sulfate promotes the growth of Bacteroides , Bifidobacterium , and Clostridium , while the number of Lactobacillus decreases [126].…”
Section: Association Of Dietary Factor-induced Reduction Of Blood mentioning
confidence: 99%